Nutrients in ‘Gigante’ forage cactus pear under different saline water irrigation depths and planting densities - Varley A. Fonseca; Sérgio L. R. Donato; Marcelo R. dos Santos; Carlos M. Oliveira; Marcos K. Kondo; Carlos E. Cotrim (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Climate variability tends to increase the occurrence of extreme drought conditions in semi-arid regions, thereby compromising crop yield, including that of drought-tolerant plants such as forage cactus pear. Irrigation of cactus with saline water has enabled good results, and its combination with changes in planting densities may promote changes in the production response of this crop. A field experiment spanning two crop cycles was carried out to evaluate nutrient concentrations in ‘Gigante’ forage cactus pear (Opuntia ficus-indica Mill) under different saline water irrigation depths and planting densities. A randomized block design was used with treatments arranged in split-split plots. Two irrigation intervals (7 and 14 days) were assigned to plots, four planting densities (20,000; 40,000; 60,000 and 80,000 plants ha-1) to subplots, and four irrigation depths of saline water of electrical conductivity 2.91 dS m-1 (0, 11, 22 and 33% of reference evapotranspiration) to sub-subplots. The irrigation depths were applied only in the period of the year without rain. Intermediate planting densities (43,002 and 54,687 plants ha-1) promote lower P, Ca and Fe concentrations in cladode tissues of forage cactus pear. Irrigating ‘Gigante’ cactus forage with saline water up to 33% ETo increases the concentrations of N, P, Ca, Mg, B, Cu, Mn and Zn in cladode tissues. Irrigation levels between 16 and 25% of ETo with saline water resulted in the highest concentrations of K, S and Na.